Populist Backlash and Trade Agreements in North America: The Prospects for Progressive Trade - Finbow, Robert G. (2023)
Populist rejection of the embedded liberal international order is evident in many Western democracies. This is partly attributable to the architects of this system, who over-promised widespread benefits while ignoring warnings from labour and fair-trade advocates about risks to economic security from transnational economic competition. This article contrasts Canadian and American conservative populist positions on free trade. Globalisation and free trade without consideration for fair trade weakened the embedded liberal compromise and undermined the Keynesian welfare state model which sustained it. While regional free trade agreements like the North American Free Trade Agreement have had marginal negative effects, they became convenient scapegoats in a strategy of “othering” adopted by Trump and other populists. Populism arose in part in response to middle- and working-class decline (alongside cultural changes and revitalised nativism), which eroded support for embedded liberalism. The heretofore pro-trade GOP followed Trump to a more protectionist and bilateral model to press for “America first,” tinged by nativist othering towards Mexico and China. This diverged from Canadian right-populist leaders, whose rhetoric generally supports freer trade despite scepticism among some supporters. Asymmetrical circumstances of the US as a global economic hegemon vs. Canada as trade-dependent middle power limits the feasibility of a protectionist, “Canada first” position while particularities of political and electoral systems create more room for nativism in the US. Polling results indicate support for free trade in both nations, with a priority for labour and social protections, which provides the potential for further engagement in progressive trade liberalisation. Hence a significant percentage of the population supports “fair-trade” approaches, not protectionism. However, many conservative politicians eschew fair-trade positions and endorse anti-labour policies. Despite gains such as the labour provisions in the Canada–US–Mexico Agreement, a right-populist alliance with fair-trade advocates and labour unions is unsustainable and would entail compromises like climate denial, anti-immigrant, and anti-equity approaches which hinder the pursuit of progressive multilateral trading regimes.